2017
DOI: 10.1002/2016jc012521
|View full text |Cite
|
Sign up to set email alerts
|

Projected changes in significant wave height toward the end of the 21st century: Northeast Atlantic

Abstract: Wind field ensembles from six CMIP5 models force wave model time slices of the northeast Atlantic over the last three decades of the 20th and the 21st centuries. The future wave climate is investigated by considering the RCP4.5 and RCP8.5 emission scenarios. The CMIP5 model selection is based on their ability to reconstruct the present (1971–2000) extratropical cyclone activity, but increased spatial resolution has also been emphasized. In total, the study comprises 35 wave model integrations, each about 30 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
56
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 48 publications
12
56
0
Order By: Relevance
“…Our work shows an overall reduction in the mean wave height but with increased extreme waves on (1) west of Portugal and (2) north of 60°N (related to retreating sea ice). Although only a single model is used in our work, it shows results consistent with the multimodel analysis of other authors (e.g., Aarnes et al, ). Gallagher et al () also projected an overall decrease in annual and seasonal mean SWH around Ireland.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our work shows an overall reduction in the mean wave height but with increased extreme waves on (1) west of Portugal and (2) north of 60°N (related to retreating sea ice). Although only a single model is used in our work, it shows results consistent with the multimodel analysis of other authors (e.g., Aarnes et al, ). Gallagher et al () also projected an overall decrease in annual and seasonal mean SWH around Ireland.…”
Section: Discussionsupporting
confidence: 89%
“…A reduction in mean SWH is not incompatible with an increase in extremes, rather, these results suggest that the PDF of wave heights may be widening (leading to longer tails in the distributions). Aarnes et al () also project a decrease in mean SWH of the order of 10% in the Central North Atlantic by the end of the century. They also note that the upper percentiles of future wave height have a higher variance than the mean climate, which is consistent with our findings here.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Our projection of a decrease in mean SWH agrees with the results of Aarnes et al (2017), who also note a smaller reduction in higher percentiles of SWH, suggesting an increase in the variance. Bricheno and Wolf (2018) discuss an alternative metric of wave changes, based on the mean of twenty annual maxima in SWH at the beginning and end of the 21st century.…”
Section: Wavessupporting
confidence: 90%
“…the next decades, with more extreme winters as described in Figures 4b, 4c, 4e, and 4f. However, most of the existing climate models indicate that there will be no increase in winter Hs in the northeast Atlantic or even a decrease as stated in Hemer et al (2013), in the frame of climate change even for the worst-case emission scenario (e.g., Aarnes et al, 2017;Wang et al, 2014). A notable exception is the study of Zappa et al (2013) who showed a systematic increase in the number of European extratropical cyclones with increasing emission.…”
Section: Discussionmentioning
confidence: 99%